PENGARUH ANGGARAN DAN PENGENDALIAN TERHADAP EFEKTIVITAS KINERJA SATUAN KERJA PERANGKAT DAERAH (SKPD) DI KABUPATEN MALANG - Fatoni, Irfan; Nurhayati, Indah Dewi (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
The research is aimed to find out the influence of budget and control on the effectiveness of performance in Satuan Kerja Perangkat Daerah (SKPD) in Malang, East Java. The sample is selected using proportional random sampling method consisting of 264 respondents. The data are obtained through observation, interview, and questionnaire consisting. Variables consisted of the budget, control, and performance effectiveness. Hypothesis testing is performed by using regression analysis. The test results showed that the budget and control positive and significant effect on the effectiveness of performance SKPD. Key words : budget, control, and effectiveness of performance SKPD